PELATIHAN PENGOLAHAN SAMPAH KERTAS KORAN MENJADI ALAT PERAGA MATEMATIKA DI SMP NEGERI 3 BIREUEN - Rahmi Hayati; Bulan Nuri; Rahmi Wahyuni; Novianti Novianti; Husnidar Husnidar (LPPM Universitas Al Muslim, 2023)
Mathematic has several goals that must be achieved, one of which is to make the students have the ability to understand concepts, to explain the interrelationships between concepts and apply these concepts appropriately in problem solving. For this reason, teachers are required to be a medium in transferring knowledge to students so that students are motivated in learning mathematics at school. This training of newsprint-waste processing was aimed at Mathematics teachers at SMP Negeri 3 Bireuen to stimulate the ceativity of the teachers in providing satisfying math teaching aids. The implementation of this community service activity was carried out in two stages, namely the preparation stage and the implementation stage, where the implementation stage consisted of two activities, namely the presentation of training material and direct practical assignments in the form of making mathematical teaching aids made from newsprint. The training on processing newsprint-waste into math teaching aids for teachers showed a positive impact on students' interest and learning outcomes at SMP Negeri 3 Bireuen. The outputs of this activity were: 1) various types of mathematical teaching aids made from newsprint that can be used in the teaching and learning process; 2) increase the creativity of teachers and students in their work; 3) produce math teaching aids that have the potential to generate high selling points for other schools.